Documentation of psychotropic pro re nata medication administration: An evaluation of electronic health records compared with paper charts and verbal reports. Issue 15 (23rd July 2018) - Martin, Krystle; Ham, Elke; Hilton, N Zoe
Abstract : Aims and objectives: To describe the documentation of pro re nata (PRN) medication for anxiety and to compare documentation at two hospitals providing similar psychiatric services, one that used paper charts and another that used an electronic health record (EHR). We also assessed congruence between nursing documentation and verbal reports from staff about the PRN administration process. Background: The ability to accurately document patients' symptoms and the care given is considered a core competency of the nursing profession (Wilkinson, Nursing process and critical thinking, Saddle River, 2007); however, researchers have found poor concordance between nursing notes and verbal reports or observations of events (e.g., Marinis et al., 2010, J Clin Nurs, 19, 1544–1552) and considerable information missing (e.g., Marinis et al., 2010, J Clin Nurs, 19, 1544–1552). Additionally, the administration of PRN medication has consistently been noted to be poorly documented (e.g., Baker et al., 2008, J Clin Nurs, 17, 1122–1131). Design: The project was a mixed‐method, two‐phase study that collected data from two sites. Methods: In phase 1, nursing documentation of PRN medication administrations was reviewed in patient charts; phase 2 included verbal reports from staff about this practice. Results: Nurses using EHR documented more information than those using paper charts, including the reason for PRN administration, who initiated the administration, and effectiveness. There were some differences between written and verbal reports, including whether potential side effects were explained to patients prior to PRN administration. Conclusions: We continue the calls for attention to be paid to improving the quality of nursing documentation. Our results support the shift to using EHR, yet not relying on this method completely to ensure comprehensiveness of documentation. Relevance to clinical practice: Efforts to address the quality of documentation, particularly for PRN administration, are needed. This could be made through training, using structured report templates and by switching to electronic databases.